ADAPTIVE BIT-RATE STREAMING. - Monchamp, Ted D. (InSight: Rivier Academic Journal)
This paper describes an overview of adaptive bit-rate streaming as a content delivery technique. General principles will be discussed as well as an introduction to several of the current leading adaptive streaming technologies and how they function. Adaptive streaming is a technique used for client-driven video streaming over HTTP, and aims to provide end users with higher-quality playback by adjusting the stream to fit the client's current network and processing conditions.